Bio–based Pentenoic Acids as Intermediates to Higher Value‐Added Mono‐ and Dicarboxylic Acids. Issue 3 (21st March 2016) - Nobbs, James D.; Zainal, Nur Zahirah Binte; Tan, Jozel; Drent, Eite; Stubbs, Ludger P.; Li , Chuanzhao; Lim, Sharon C. Y.; Kumbang, Daniel G. A.; van Meurs, Martin
Abstract: The acid catalyzed reactive distillation of γ‐valerolactone yields pentenoic acids (PEAs) which can be obtained in >90 % purity and >97 % selectivity. The PEAs (five isomers) can be converted into a number of useful products with commercial relevance. The hydroxycarbonylation of PEAs yields adipic acid (a Nylon monomer) in very high selectivity and with good activity. Self‐metathesis of PEAs yields C6 – C8 unsaturated dicarboxylic acids which after hydrogenation produces a mixture of adipic acid, pimelic acid and suberic acid. If the PEAs are first subjected to ethenolysis; acrylic acid, 3‐butenoic acid, and 4‐pentenoic acid are produced. The self‐metathesis of 3‐butenoic acid produces β‐hydromuconic acid in >99 % selectivity which can be hydrogenated to adipic acid, whereas the self‐metathesis of 4‐PEA followed by hydrogenation gives suberic acid with 99 % selectivity. 3‐Butenoic acid can also be hydroxycarbonylated to produce glutaric acid in 99 % selectivity. Abstract : Nylon monomers (adipic acid and suberic acid) derived from the upgrading of bio‐based pentenoic acids: ring opening of gamma valerolactone produces a mixture of five pentenoic acid isomers, which via olefin metathesis and carbonylation can be converted into single dicarboxylic acids.